Seasonal and age related changes in size of reproductive structures of red deer hinds (Cervus elaphus) - Langvatn, Rolf (Rangifer, 1992)
Morphometric studies of uteri, ovary weights, and follicle diameters were carried out to investigate possible methodological applications. Size and anatomical appearance of the uterus varied with age and phase in the estrous cycle, both in parous and nulliparous females. The uterus thus may provide valuable information on reproductive status for known-aged animals. Weight of ovaries increased in young, but declined in old females, showing significant covariance with body weight in young and prime ages. Ovary weights increased from low levels shortly after parturition to a maximum towards the end of the gestation period. Ovaries containing a corpus luteum were heavier than those without. Compared to ovary weights, mean diameter of largest ovarian follicle varied in an opposite pattern during the yearly cycle. Maximum follicle diameter was largest in non-ovulated females. Weight of ovaries and follicle size appear to be of limited value as criteria in analysis of reproductive status and performance.